2014
DOI: 10.3762/bjoc.10.61
|View full text |Cite
|
Sign up to set email alerts
|

End-group-functionalized poly(N,N-diethylacrylamide) via free-radical chain transfer polymerization: Influence of sulfur oxidation and cyclodextrin on self-organization and cloud points in water

Abstract: SummaryIn this work we report the synthesis of thermo-, oxidation- and cyclodextrin- (CD) responsive end-group-functionalized polymers, based on N,N-diethylacrylamide (DEAAm). In a classical free-radical chain transfer polymerization, using thiol-functionalized 4-alkylphenols, namely 3-(4-(1,1-dimethylethan-1-yl)phenoxy)propane-1-thiol and 3-(4-(2,4,4-trimethylpentan-2-yl)phenoxy)propane-1-thiol, poly(N,N-diethylacrylamide) (PDEAAm) with well-defined hydrophobic end-groups is obtained. These end-group-function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Amphiphilic host molecules, such as cyclodextrins, featuring a hydrophilic outer shell and a hydrophobic cavity, can complexate with hydrophobic guests present in a thermoresponsive polymer, thereby increasing its hydrophilicity and T CP . Many examples have been reported on complexation of cyclodextrins with endgroup guest-functionalized thermoresponsive polymers, including PNIPAAm-azo dye [83], PNIPAAm-vinylcyclopropane [84], or poly(N,N-diethylacrylamide)-4-alkylphenol with methylated bCDs [85]. As expected, T CP variations were found to be dependent on the excess of cyclodextrin host added, and typically increased by less than 5 K, although a T CP increase of close to 10 K was observed in a tert-butyl phenyl-terminated poly(N,N-diethylacrylamide) (PDEAAm) thermoresponsive polymer in the presence of 2 equiv.…”
Section: Modulating Polymeric Architectures By Supramolecular Interacmentioning
confidence: 99%
“…Amphiphilic host molecules, such as cyclodextrins, featuring a hydrophilic outer shell and a hydrophobic cavity, can complexate with hydrophobic guests present in a thermoresponsive polymer, thereby increasing its hydrophilicity and T CP . Many examples have been reported on complexation of cyclodextrins with endgroup guest-functionalized thermoresponsive polymers, including PNIPAAm-azo dye [83], PNIPAAm-vinylcyclopropane [84], or poly(N,N-diethylacrylamide)-4-alkylphenol with methylated bCDs [85]. As expected, T CP variations were found to be dependent on the excess of cyclodextrin host added, and typically increased by less than 5 K, although a T CP increase of close to 10 K was observed in a tert-butyl phenyl-terminated poly(N,N-diethylacrylamide) (PDEAAm) thermoresponsive polymer in the presence of 2 equiv.…”
Section: Modulating Polymeric Architectures By Supramolecular Interacmentioning
confidence: 99%
“…Polymers that undergo a thermally induced phase separation, such as a lower critical solution temperature (LCST), have recently found application in as drug delivery vehicles, antibacterial materials, latex particle coatings, dielectrics, and thermally curable thin films as part of systems containing conductive materials . Several N‐substituted poly(acrylamide)s experience sharp and biologically relevant LCSTs around 30–60 °C . The properties of the polymer, such as molecular weight distribution, copolymer composition, and molecular architecture, have an impact on the final polymer's thermoresponsiveness .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of thioethers, in contrast to regular ethers the nature of sulfur provides the possibility of functionalization, while representing a more stable option than disulfides and thiol groups, which is essential for biomedical applications since a precise targeting requires a structure which remains unchanged until it is required . During the last years the incorporation of thioethers for stimuli‐responsive materials has been a deal of research effort, for instance, Tirelli and co‐workers reported the potential of polythioethers as redox‐responsive nanocarriers for inflammation targeting, remarking that hydrophobic thioethers could be oxidized in the milieu of inflamed tissue, changing the hydrophobic/hydrophilic balance with disassembly of the nanostructure, and Long and co‐workers, who studied sulfone‐functional poly(methyl methacrylate) (PMMA) derivatives, found them to be nonviral nucleic acid delivery agents and confirmed their high potential for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophobic thioethers shifted the lower critical solution temperature (LCST) values to very low temperatures, but could be regulated upon oxidation due to the huge increase in dipolar moment upon conversion into sulfoxide group using H 2 O 2 . A similar report was presented by Ritter and co‐workers, in which they reported a thioether end‐functionalized poly( N , N ‐diethylacrylamide) (PDEAAM), which shifted around 5 °C in the cloud point values upon oxidation, however in this work it is reported a random distribution of thioethers along the polymer chains, and a shift of up to 23 °C, which to the best of our knowledge an influence of this extent over LCST upon oxidation has never been reported before. In addition, the oxidation of polymers was carried out using a very small concentration (1 wt%) of hydrogen peroxide, which in case of tumors is the type of reactive oxygen species (ROS) which is found in greater amount …”
Section: Introductionmentioning
confidence: 99%